2014
DOI: 10.1186/2251-6581-13-74
|View full text |Cite
|
Sign up to set email alerts
|

Is the Iranian Traditional Medicine warm and cold temperament related to Basal Metabolic Rate and activity of the sympathetic-parasympathetic system? Study protocol

Abstract: The article Efficacy and safety of duloxetine and Pregabalin in Iranian patients with diabetic peripheral neuropathic pain: a double-blind, randomized clinical trial, written by Khojasteh Joharchi, Moosareza Memari, Eznollah Azargashb, and Navid Saadat, was originally published electronically on the publisher's internet portal (currently SpringerLink) on 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…As it is reported by Mohammadi Farsani G, et al, cold temper subjects had a non-signi cant lower BMR; while they had signi cantly lower heart rate, and systolic and diastolic blood pressure [20]. But they mentioned that they would have an interventional phase investigating the acute phase effect of thyme/ sumac consumption as cold and hot temper agents on metabolic responses and sympathetic nervous system activity of the body that its results are not published yet [23]. As it is aforementioned, modi cation of the routine diet is superior to herbal/chemical drug usage in TPM school.…”
Section: Discussionmentioning
confidence: 99%
“…As it is reported by Mohammadi Farsani G, et al, cold temper subjects had a non-signi cant lower BMR; while they had signi cantly lower heart rate, and systolic and diastolic blood pressure [20]. But they mentioned that they would have an interventional phase investigating the acute phase effect of thyme/ sumac consumption as cold and hot temper agents on metabolic responses and sympathetic nervous system activity of the body that its results are not published yet [23]. As it is aforementioned, modi cation of the routine diet is superior to herbal/chemical drug usage in TPM school.…”
Section: Discussionmentioning
confidence: 99%
“…For example, people with warm and wet temperaments have a larger body size [10, 35]. In recent studies, the relationship between temperament and certain concepts in conventional medicine like basal metabolism have been investigated [36]. This relationship, if proven, can be investigated due to the effect of metabolism on the amount of water required by the body [33].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Recent investigations have shown that hot (warm) and cold temperaments can be associated with BMR and similarly with sympathetic-parasympathetic nervous system activity. 27,28 Some of these relationships are shown in Table 1.…”
Section: The Evaluation Of Basic and Neurohormonal Parameters In Hot mentioning
confidence: 99%